Climate change and common sense : essays in honour of Tom Schelling - Schelling, Thomas C., 1921-; Hahn, Robert William; Ulph, Alistair (Oxford : Oxford University Press, 2012)
This overview of the political and economic processes driving climate change policy highlights the work of Nobel Laureate Tom Schelling. It identifies the institutional arrangements needed to design more effective policy and examines the ethical arguments that are critical to understanding and framing the climate debate.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Environmental economics; Climatic changes -- Economic aspects